1998
DOI: 10.2337/diacare.21.3.374
|View full text |Cite
|
Sign up to set email alerts
|

Transient Improvement in Glycemic Control: The impact of pregnancy in women with IDDM

Abstract: Nearly all women with IDDM can achieve near normoglycemia during pregnancy, irrespective of previous glycemic control, although those with high HbA1 levels at booking are less likely to achieve this. After delivery, glycemic control deteriorates. Efforts to improve glycemic control should be intensified in the preconception period and maintained after delivery. The poor postpartum attendance at diabetes clinics requires specific action.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
8
0

Year Published

2000
2000
2018
2018

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(12 citation statements)
references
References 12 publications
4
8
0
Order By: Relevance
“…Sixty-percent of the women (30 of 50) who were controlled during pregnancy had a subsequent uncontrolled HbA1c within 2 years, including all the women who entered pregnancy uncontrolled. Taken together, our findings—that women are able to achieve control when supported and highly motivated during pregnancy, but then trend back toward uncontrolled diabetes due to competing priorities and/or loss to follow-up—echo the conclusions of other studies conducted on pre-existing diabetes in pregnancy [2628]. …”
Section: Discussionsupporting
confidence: 85%
“…Sixty-percent of the women (30 of 50) who were controlled during pregnancy had a subsequent uncontrolled HbA1c within 2 years, including all the women who entered pregnancy uncontrolled. Taken together, our findings—that women are able to achieve control when supported and highly motivated during pregnancy, but then trend back toward uncontrolled diabetes due to competing priorities and/or loss to follow-up—echo the conclusions of other studies conducted on pre-existing diabetes in pregnancy [2628]. …”
Section: Discussionsupporting
confidence: 85%
“…13 Nevertheless, there is little information about what happens with metabolic control after delivery. A recent study 14 confirmed prior existing data 15 indicating that after birth there is a marked worsening of glycemic control in such patients. This study observed similar weight gain in pregnant patients with diabetes with respect to a nondiabetic population 16 but less weight lost during the first year after delivery.…”
Section: Introductionsupporting
confidence: 60%
“…12---15 This is probably due to the fact that 44.4% of the subjects were treated with CSII prior to gestation and this group of patients often have greater adherence to follow-up. 7,15 Regarding the assessment of the effectiveness of this program, we found that the T1D women included in the PPP had lower HbA1c before pregnancy, which was maintained during the first and third trimesters of pregnancy and one year after delivery, but we failed to prove statistically significant differences in data regarding delivery and newborn outcomes. The limited number of individuals in our study may explain the inability to demonstrate these differences.…”
Section: Discussionmentioning
confidence: 79%
“…On the other hand, extensive education programs during pregnancy could help new mothers maintain improved glycemic control after delivery (7). Only one small observational study exists for type 1 diabetes, showing that after a substantial improvement during pregnancy, glycemic control deteriorated, reaching pregestational levels after delivery (8). An urgent need exists for new, up-to-date studies, as the therapeutic aims and tools available 20 years ago have changed dramatically.…”
mentioning
confidence: 99%